Implementasi Pembinaan Korban Penyalahgunaan Narkotika Melalui Rehabilitasi Pada Lembaga Pemasyarakatan - Nurlaila Nurlaila; Kristiawanto Kristiawanto; Mohamad Ismed (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
Discussion of the Implementation of Guidance for Victims of Narcotics Abuse in Correctional Institutions via Rehabilitation. This legal research takes a normative juridical approach, which means that it examines still-in-force legal concepts and norms. According to Article 54 of Law Number 35 of 2009 concerning Narcotics, addicts and victims of drug abuse must undergo medical and social rehabilitation. Additionally, pursuant to Law Number 12 of 1995 concerning Corrections, special narcotics prisons are provided for violators of narcotics crime laws. Fostering victims of drugs misuse in Correctional Institutions is accomplished in two ways: medical rehabilitation and social rehabilitation in accordance with court rulings. Where medical rehabilitation is provided to victims of narcotics misuse in accordance with the therapy plan established by the Doctor Team from the Integrated Assessment Team and in accordance with the program applicable to the rehabilitation institution. Meanwhile, a rehabilitation institute built by the Provincial National Narcotics Agency provides social rehabilitation for victims of narcotics usage.